Analisis Efisiensi Dan Efektivitas Anggaran Penjualan - Agung Muslim, Muhammad; Jumady, Edy; Fajriah, Yana (Innovative: Journal Of Social Science Research, 2024)
This research aims to find out the effectiveness and efficiency of the sales budget for palm oil plantations in one of the State-Owned Enterprises (BUMN), namely PTPN 1 Regional 8. This research uses a descriptive analysis method. The data collection technique in this research uses two types of primary data and secondary data to calculate effectiveness and efficiency and to obtain phenomena that occur in the field in the period 2019 to 2023. The descriptive analysis method can be carried out with a quantitative approach in the form of data collection and measurement in the form of numbers. Data shows that the palm oil plantation sales budget to effectiveness ratio varies every year. In 2019, the effectiveness ratio showed that the category was ineffective because the figure was below 60 percent. However, in 2020 there was an increase in the effectiveness ratio above 100 percent. But in total from 2019 to 2023 the ratio is less effective. Data obtained through calculations between the volume of sales costs and the sales budget for that year. Meanwhile, for efficiency data shows the efficiency ratio also varies from year to year. However, the total for 2019 to 2023 shows a fairly efficient ratio. The efficiency ratio is obtained by calculating total production costs with total sales volume. One of the factors that influences the ratio score is due to changes in policies related to the sale of oil palm plantation products.